PARENTERAL NUTRITION IN PATIENTS WITH ACUTE KIDNEY INJURY - Zakon, K.; Berezyak, T.; Radchenko, G.; Romanova, V. (Ukrainian Journal of Nephrology and Dialysis, 2015)
This review is dedicated to changes in metabolism of major nutrients (proteins, fats and carbohydrates) in patients with acute kidney injury. Differences with other acute diseases and influence of renal replacement therapy are highlighted. Results of experimental and clinical trials are debated. The aim of nutritional support and macronutrients requirements are specified, as well as indications to parenteral nutrition, alternative approaches to control protein catabolism and influence of nutritional support on outcome.